MENCIPTAKAN RESONANSI MEREK MELALUI KEPERCAYAAN BERDASARKAN PADA DAYA TARIK MEREK - Arisman, Ari; Umbara, Dona Setia (Jurnal Ekonomi Manajemen, 2022)
The purpose of this study was to find out how the influence of brand attractiveness in building brand trust and increasing brand resonance in Indonesian local shoe brand users. This is a verification research, using survey methods, and collecting data by distributing a questionnaire of 125 respondents who are consumers of local Indonesian brand shoes who have purchased the product more than once using purposive sampling technique. The analytical tool used in this research is Structural Equation Modeling (SEM) where the analysis results show that brand attractiveness is proven to be the right strategy in creating brand trust and brand resonance. Brand trust which is based on the evaluation of attractiveness also proves to be an antecedent of the formation of brand resonance in consumers of local Indonesian brand shoes.